Cardiac biomarkers : case studies and clinical correlations - Maisel, Alan S.; Jaffe, Allan S. (2016 Springer EBA Collection., 2016)
This book presents a comprehensive compendium of case studies to inform clinicians how to optimally deploy the major clinically utilized biomarkers in cardiology. Biomarkers now play an integral role in the treatment and management of patients with congestive heart failure and acute ischemic heart disease because they provide crucial information about the status of individual patients. For that reason, it is important for clinicians to understand the basis for the use of these markers. Every reader may not have the laboratory and/or clinical expertise to understand all the details associated with the use of these markers, which is why this book takes a case oriented approach and by doing so provides a practical resource to guide the clinician through the options available. Cardiac Biomarkers discusses how to use these biomarkers optimally and, in particular, how to understand when values provide actionable information. The book an essential guide for all physicians and healthcare practitioners in the field of cardiology.